Synthesis of an off-grid solar thermal cogeneration and intelligent smartgrid control system for rural applications - Prinsloo, Gerhardus Johannes (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.